Synthesis of Microporous Carbon Foams as Catalyst Supports - Glenk, Friedrich; Knorr, Tilman; Schirmer, Matthias; Gütlein, Stefan; Etzold, Bastian (Chemical Engineering & Technology, 2010)
Microporous carbon foams were synthesized as structured catalyst supports by the carbide-derived carbon (CDC) method. The self-supporting foams showed a narrow pore size distribution which seems to induce shape-selective effects during reactions. The applicability of these materials as supports for active metals was tested in a hydrogenation reaction of different olefins with a CDC powder wet impregnated with platinum
EAM Import::2019-03-12
Keywords: Carbide-derived carbon; CDC method; Foams; Microporous carbon; CARBIDE-DERIVED CARBONS; HYDROGEN STORAGE; ACTIVATED CARBON; MONOLITHS; NITROBENZENE; POROSITY; REACTOR